Influence of environmental value, environment leadership, stakeholders’ participations on green service delivery and sustainability performance among casual dining restaurants - Nawang Mustapen, Rosini (2021)
Previous literature showed that greening efforts as a sustainability practice has been extensively deliberated to explore and identify its relationship with sustainability performance. Despite extensive prior studies, the implementation of sustainability practices remains arguable in business operation. Some scholars suggested that accomplishment in sustainability practices are dependent on a few factors such as environmental value, environmental leadership, and stakeholder participation. However, from the perspective of the top management, mainly the owners of casual dining restaurants, these practices remain inadequate in understanding the green service delivery process. Also, top management plays a crucial role in implementing decisions in sustainability performance through their commitment to the green service delivery efforts. Hence, this study is expected to provide an understanding of the green service delivery process by predicting its influencing factors,and examining the effects of the green service delivery process on sustainability performance as well as examining the mediating effect of its process variable. This study used naturalresources- based view (NRBV) theory as its underpinning theory, supported by value-belief-norm, upper echelons theory and stakeholder theory to explain the influencing factors and mediating effects of the green service delivery process. Data was collected over a period of six months from the top management of independent casual dining restaurants, namely, the owner, CEO or general manager. These restaurants are not affiliated with any national brand nor are they in any franchise business arrangement. A convenience sampling technique was utilized to hand-deliver five hundred questionnaires. Of the total 328 questionnaires returned, three hundred and eleven questionnaires were useable. SmartPLS 3.0 was used to analyse the data and test the study hypotheses. Results showed that environmental value, environmental leadership and stakeholder participation are significantly positive on the green services delivery process. Results also showed that the green services delivery process mediated the relationship between environmental value, environmental leadership and stakeholder participation and sustainability performance. The findings further showed that the greening service effort through the green service delivery process significantly affected sustainability performance. Hence, these finding are important as a turning point for restaurateurs in the casual dining restaurant which they can apply in their green service delivery process. Furthermore, the mediating effect of the green services delivery process between environmental value, environmental leadership and stakeholder participation and sustainability performance showed a high need to promote robust greening efforts to enhance understanding of sustainable development among top management who are responsible in making crucial decisions in their business operations. Therefore, the theoretical and practical contributions of this study are essential given the actual results of the model. Also, the theoretical contributions extended the present collaborative model. Finally, this study provided practical suggestions on how green service delivery can influence sustainability performance among casual dining restaurants and showed how businesses can apply sustainability practices for better performance.